ANALISIS YURIDIS PROSES ADMINISTRASI PERUBAHAN NAMA ANAK (Studi Kasus Di Pengadilan Negeri Jember) - Adhim, Muhammad Syauqun; Najib, Ainun; Efendi, Yulius (Fakultas Ilmu Sosial dan Humaniora, 2023)
In cases that often occur, many parents want to change their child's name because they think their child often gets sick because they use that name. Another common reason why someone changes their name from their previous name is because they have needs related to their individual interests. This research aims to analyze the juridical aspects related to the process of changing a child's name and the legal consequences of changing a child's name in the District Court. The research carried out is legal research that is analytical in nature and uses a type of normative-empirical juridical research, namely combining or approaching related laws and regulations, as well as the views of experts in the legal field. Primary data is based on interviews and documentation. Based on the research results, it shows that 1) The process of changing a child's name at the Jember District Court involves structured stages, starting from submitting an application by the child's parent or guardian, administrative examination by the court, determining the decision by the judge to announcing it to the public. Each stage requires administrative requirements and documents that have been previously determined, with a settlement process that lasts two weeks and there are court costs incurred. 2) The legal consequences that arise from changing a child's name are the legality of the child's legal status regarding changes in several authentic evidence, such as Deeds. The birth of a child with the name on the Family Card (KK) in question.